Poland: Tax Law and Policy in Poland – Bold and Expected Changes - Oktaba, Robert (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This publication addresses the issues related to the concept and processes of the coexistence of tax harmonisation in the EU and the sovereign tax policies of individual Member States. An important task in the context of the creation and application of EU tax law regulations is determining the tax sovereignty of Member States and the legitimacy of implementing an autonomous tax policy adapted to the current social and economic needs of a given country. These phenomena also affect the tax competitiveness of a given country in the international arena. Importantly, implementing a sovereign tax policy allows state authorities to take flexible actions to counteract tax avoidance and combat tax fraud in a given country. Thus, eliminating unfair competition from the market strengthens the position of law-abiding taxpayers. Moreover, this interdependence contributes to economic growth and employment opportunities. As a result, it is possible to increase tax revenues from the taxation of both the growing economic turnover and the income of natural persons and entrepreneurs. Therefore, the possibility of implementing a sovereign tax policy allows for the creation and maintenance of a tight and functional tax system, which is a key element of economic and social order. It is worth emphasizing here that macroeconomic data, both domestic and international, indicate that Poland’s sovereign tax policy has yielded excellent results over the last seven to eight years.Keywords: tax sovereignty, tax avoidance, tax policy, budget revenues